2020
DOI: 10.1111/1365-2664.13578
|View full text |Cite
|
Sign up to set email alerts
|

Trophic transfer of pesticides: The fine line between predator–prey regulation and pesticide–pest regulation

Abstract: Understanding pesticide impacts on populations of target/non‐target species and communities is a challenge to applied ecology. When predators that otherwise regulate pest densities ingest prey contaminated with pesticides, this can suppress predator populations by secondary poisoning. It is, however, unknown how species relationships and protocols of treatments (e.g. anticoagulant rodenticide [AR]) interact to affect pest regulation. To tackle this issue, we modelled a heuristic non‐spatialized system includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…In any case, we found that weasels in Spain have been exposed to bromadiolone as in northern and central Europe (Elmeros et al, 2011;Fernandez-de-Simon et al, 2019;Koivisto et al, 2018;McDonald et al, 1998). Bromadiolone and another AR (brodifacoum) could eventually have produced population declines of small mustelids, as it has been observed empirically in France and New Zealand (Brown et al, 1998;Fernandez-de-Simon et al, 2019;Murphy et al, 1998) and also suggested by a biomathematics modelling approach in the French study context (Baudrot et al, 2020). In north-east Spain, weasel declines have also been recorded during the last several decades, although the factors potentially explaining such declines are not completely known (Torre et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…In any case, we found that weasels in Spain have been exposed to bromadiolone as in northern and central Europe (Elmeros et al, 2011;Fernandez-de-Simon et al, 2019;Koivisto et al, 2018;McDonald et al, 1998). Bromadiolone and another AR (brodifacoum) could eventually have produced population declines of small mustelids, as it has been observed empirically in France and New Zealand (Brown et al, 1998;Fernandez-de-Simon et al, 2019;Murphy et al, 1998) and also suggested by a biomathematics modelling approach in the French study context (Baudrot et al, 2020). In north-east Spain, weasel declines have also been recorded during the last several decades, although the factors potentially explaining such declines are not completely known (Torre et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, bird species that roost in large groups, such as Dickcissels ( Spiza americana ), can be killed in great numbers when their nesting sites or watering holes are poisoned ( Basili & Temple, 1999 ). Furthermore, poisons can have severe consequences for carnivores and scavengers that feed on the carcasses of poisoned animals ( Baudrot et al, 2020 ; Kalaivanan et al, 2011 ). In addition to the dangers that chemical pesticides pose to the environment, they can also pose a serious threat to the health of human workers and consumers ( Rani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such extinctions may have far-reaching effects on the ecosystem if the species is an essential part of the food web or plays important ecological roles, such as seed dispersal, with their disappearance causing cascading effects on the community ( Castillo-López et al, 2017 ). Furthermore, the use of poison to kill crop-damaging vertebrates can have severe consequences not only for the target species ( Lima et al, 2019 ), but also for other animals that may consume them, such as predators or scavengers ( Baudrot et al, 2020 ; Kalaivanan et al, 2011 ), and affect the health of human communities and cause social conflicts ( Rani et al, 2021 ). Thus, there is a need to find alternative, non-lethal crop protection techniques that can effectively protect crops while preserving the consumer vertebrate species that damage them.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of pesticides in continental Croatia (Romić et al, 2015), for example, organophosphate (OP) and carbamate (CB), insecticides which are extensively used to control pests and disease vectors at agricultural lands (Hill, 2002), there is a high possibility for pesticide exposure. Apex predators, such as white storks, could ingest contaminated prey and subsequently suffer secondary poisoning (Baudrot et al, 2020). As their nestlings reside in the nest and are completely dependent on the local food sources foraged by their parents, they are suitable bioindicators and sentinels of contaminants in the local environment (Blázquez et al, 2006; Lewis & Pomeroy., 2017).…”
Section: Introductionmentioning
confidence: 99%